STUDI NAMA GEOGRAFI MELALUI LAYANAN PEMETAAN URUNDAYA DI DESA GIRIPURWO, PURWOSARI, GUNUNGKIDUL D.I. YOGYAKARTA - Ari Cahyono (SPATIAL: Wahana Komunikasi dan Informasi Geografi, 2018)
A geographical name is a name that identify specific feature on the earth. That features could be a settlement, administrative region, natural feature, artificial feature, unbounded region, or virtual region. Under the Law Number 4 of 2011 concerning Geospatial Information, the geographical name is one of the layer that must appear on the base map. The acquisition of geographical names can be facilitated by crowdsourcing map that are conducted by corporations or the public. The objectives of this study are 1) to carry out an inventory of geographic names through crowdsourced maps, and 2) to examine the opportunities and challenges of the study of geographic names in rural areas. We observed data from crowdsourcing maps, e.g., Google Maps, Here Maps, and OpenStreetMaps that cover Giripurwo Village. We used spatial comparison in this research. We also compared its appearances on various mapping scales. A field survey was conducted to get more qualitative information about geographical names and to test the accuracy of maps. The results showed that there were differences between the crowdsource map services in presenting the geographical names at the same scale level. We face constraints in this mapping, i.e. limited accessibility in the entire region and sparsely populated in a karst region. Conversely, the high participation of rural communities is beneficial in this mapping process.